STUDENT TEACHERS’ ENGAGEMENT IN USING VOCABULARY LOG FOR VOCABULARY LEARNING AND TEACHING - Sari, Sandra Intan; Suryaman, Maman (PROJECT (Professional Journal of English Education), 2021)
Vocabulary knowledge is known as an essential element in language learning to support four language skills listening, speaking, reading and writing. Indeed, many known ways to encourage and help language learner to keep tract vocabulary development. However, little is known for keeping vocabulary using vocabulary log. Hence, the present study conducted to explore how English language learners’ engagement in using vocabulary log. Three participants, were student teachers who majoring English education, involved in this study. The study employed a narrative inquiry design, and conducted a semi-structured interview to reveal student teachers’ experience. The data were analyzed by using thematic analysis. The result of the present study showed two aspects of student teachers’ engagement in using vocabulary log for vocabulary learning and teaching: (1) linguistic (expansion of their vocabulary development where participants as learners) and (2) pedagogical (internalization of the tool and their readiness to adopt vocabulary log in class where participants as future teachers). Keywords:  Vocabulary Log, Learning Vocabulary, Teaching Vocabulary